2021
DOI: 10.9767/bcrec.16.3.10848.481-490
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of NiFe2O4 Nanoparticles by Solution Combustion Method as Photocatalyst of Congo red

Abstract: NiFe2O4 nanoparticles had been successfully synthesized by solution combustion method using urea fuel (organic precursor). The synthesized NiFe2O4 were characterized by X-ray diffraction (XRD), Scanning electron microscopy-Electron Dispersive X-ray Spectroscopy (SEM-EDs), Transmission Electron Microscopy (TEM), Fourier Transform Infra-Red (FTIR), Vibrating Sample Magnetometer (VSM), UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS), and Point of Zero Charge (pHpzc). NiFe2O4 nanoparticles irradiated with vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Another research showed that NiO and Fe3O4 were observed at 330 nm and 440 nm, respectively (Barzinjy et al, 2020). In this research, the Fe3O4/SiO2/NiO band gap was 2.83 eV, which is smaller than the band gap of NiO ~ 3.5 eV and larger than the band gap of ferrite compounds ~ 2 eV (Hariani et al, 2021).…”
Section: Catalyst Characterizationmentioning
confidence: 47%
See 2 more Smart Citations
“…Another research showed that NiO and Fe3O4 were observed at 330 nm and 440 nm, respectively (Barzinjy et al, 2020). In this research, the Fe3O4/SiO2/NiO band gap was 2.83 eV, which is smaller than the band gap of NiO ~ 3.5 eV and larger than the band gap of ferrite compounds ~ 2 eV (Hariani et al, 2021).…”
Section: Catalyst Characterizationmentioning
confidence: 47%
“…Figure 2 shows the FTIR spectra of Fe3O4, Fe3O4/SiO2, and Fe3O4/SiO2/NiO. The wave numbers between 3400 cm -1 and 1600 cm -1 appear in all peaks, indicating the presence of O-H groups from free water, which is absorbed by the catalyst (Hariani et al, 2021;Elzahrani 2017;Ojemaye et al, 2017). In Figure 2(a), Fe-O stretching vibration is observed at a wave of 557.43 cm -1 .…”
Section: Catalyst Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…This The magnetic properties of NiFe2O4, NiFe2O4/SiO2, and NiFe2O4/SiO2/NiO are presented in Figure 5. NiFe2O4 has a saturation magnetization value of 50.37 emu/g, which was greater than the value obtained after synthesis using solution combustion of 47.32 emu/g [42]. The bulk saturation value was 56 emu/g [43].…”
Section: Photocatalytic Activitymentioning
confidence: 61%
“…[39][40][41] As for the conventional liquid electrolysis, catalysts are based on non-PGMs. In particular, spinel-type catalysts are often used due to easy synthesis methodologies: solid phase method, [42][43][44][45] in the vapor phase [46] or still in the liquid phase employing, for example, hydrothermal synthesis, sol-gel, precipitation, or electrodeposition, allowing to choose from a large variety of inexpensive reagents, producing catalysts with high activity for oxygen evolution reaction and capable of showing good stability in an alkaline environment.…”
Section: Introductionmentioning
confidence: 99%